Designing Water Quality Monitoring Application Using Esp8266 - Revi Margelia; Muhammad Ihsan (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2026)
Water is the main need for human life. The decline in water quality due to household, industrial, and environmental waste requires a monitoring system that is able to work quickly, sustainably, and accurately. Continuous monitoring of water quality has an important role in supporting effective water resource management. This research develops an Internet of Things (IoT)-based water quality monitoring system by utilizing ESP8266 microcontrollers. IoT-based water quality monitoring systems in aquascapes are able to control the temperature and pH of the water so that they remain within the ideal range for fish life. In this study, how to design and build an Internet of Things based water quality monitoring system using ESP8266 microcontroller. The developed system is expected to be able to read water quality parameters in the form of pH values and water turbidity levels in real-time through integrated sensors, then send the data to the IoT monitoring application and Telegram notifications so that it can be easily accessed by users. Thus, the developed system is suitable for IoT-based water quality monitoring.